Axisymmetric Static and Dynamic Buckling of Ortotropic Shallow Spherical Caps with Initial Imperfections - Dumir, P.C.; Ghandi, M.L.; Nath, Y. (Engineering Transactions, 1984)
This study deals with the static and dynamie axisymmetric bucking of elastic ortotropic thin spherical caps with initial imperfections. A simple type of axisymmetric imperfections in considered. The governing equations are formulated in terms of normal displacement w and stress function w. The orthogonal point collocation method is used for spatial discretisation and the Newmark-B scheme is used for time-marching. The uniformly distributed static and step function pressure loads are considered in the study. The solutions of perfect spherical caps under step loading are in good agreement loads of isotropic and orthotropic shallow spherical caps has been investigated for the shell rise to thickness ratio up to ten.